Handbuch Sprache in der Medizin - Busch, Albert; Spranz-Fogasy, Thomas (Handbücher Sprachwissen, 2015)
Language in medicine is more than a means of communication - it is a diagnostic and therapeutic instrument. Language is essential to medical research and education and in social discourse in a medicalized society. The handbook surveys language in medical and media communication related to the health care system. Contains contributions from experts in medicine, linguistics, conversation research and the media and communication sciences. Albert Busch, Göttingen University, Germany; Thomas Spranz-Fogasy, Mannheim University, Germany.
Keywords: Electronic books; Aufsatzsammlung; Sprache; Kommunikation; Medizin